"Heart Sutra Pop": Religious Textual Democratization by a Sexy Vocal Android - Shultz, John (Journal of religion and popular culture, 2021)
In 2010, the publication of "Heart Sutra Pop," an online animated video featuring the cyber-idol Hatsune Miku singing the Heart Sutra, launched a viral enthusiasm for the text that is unmatched throughout its more than twelve-hundred-year history in Japan. This article explores the digital rebirth of the sutra and the rise of an unlikely virtual spiritual leader. I argue that this cyber-idol-driven sutra boom is both doctrinally justifiable and consistent with a wave of new media initiatives by Japanese Buddhists.